A mineral water treatment tablet capable of continuously dissolving strontium and a preparation method and application thereof

CN122877898APending Publication Date: 2026-10-09SHANDONG ETERNAL WORLD NEW MATERIAL IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611277604.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

这种应用模式对设备有依赖,使用场景受限,且动态水流中矿化元素的溶出速率易受原水pH、温度、流量等条件影响,难以实现精准稳定的锶浓度控制

Benefits of technology

(1)本发明采用天然矿物原料经物理加工制成,不涉及电解等复杂系统,无电气安全隐患,亦无电解副产物(活性氧、氢气)影响口感的问题。产品形态为片状,浸泡使用过程中无粉末渗出,避免了传统矿物粉末茶包方式导致的水体浑浊沉淀问题,市场接受度高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122877898A_ABST
    Figure CN122877898A_ABST
Patent Text Reader

Abstract

The application provides a mineral water treatment tablet capable of continuously dissolving strontium and a preparation method and application thereof, and relates to the technical field of water treatment materials. The mineral water treatment tablet capable of continuously dissolving strontium contains, in terms of mass fraction, 10-30% of lazulite extract, 20-40% of strontianite extract, 10-30% of magnesite extract, 0.5-15% of quartz and 10-30% of a binder. The tablet can realize continuous and stable dissolution of strontium elements in daily scenarios through soaking, and the dissolution concentration can be controlled within the range of greater than or equal to 1 mg / L, so as to provide a more reliable, convenient-to-operate and dose-specific solution for daily trace element supplementation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water treatment materials technology, and more specifically, to a mineral water treatment sheet that sustainably dissolves strontium, its preparation method, and its application. Background Technology

[0002] Strontium is an essential trace element for the human body, playing a vital physiological role in bone health, cardiovascular function, and metabolism. There are three main ways the human body ingests strontium: first, through drinking water rich in strontium, such as natural mineral water, where strontium exists in dissolved ionic form and has high bioavailability; second, through foods such as grains, leafy green vegetables, seafood, and dairy products, but the content is low and absorption efficiency is affected by the food matrix; and third, through artificial supplements such as strontium citrate and strontium ranelate, but these preparations are prescription drugs and only suitable for specific clinical populations. In summary, supplementing strontium through daily drinking water is the most convenient, safe, and efficient method.

[0003] However, existing technologies still have significant shortcomings in the field of strontium mineralization for drinking water.

[0004] In the field of mineralization materials, existing technologies mostly employ multi-component composite systems. For example, Chinese patent CN114470889A discloses a high-flux, long-life strontium-rich mineralization filter element, which comprises porous strontium ore particles, porous calcium ore particles, expanded vermiculite particles, and activated carbon particles; Chinese patent CN117942664B discloses a strontium mineralization slow-release filter element composed of celestite powder, activated carbon, and adhesive powder; and Chinese patent CN117164337B discloses a slow-release mineralization material capable of dissolving alkali metals / strontium / selenium, with raw materials including strontium-containing raw materials, silica, zeolite, quartz, and binders. A common characteristic of these technologies is the large number of components (usually more than six) or the mixture of functional elements (strontium co-released with selenium, zinc, lithium, and other elements), making precise control of the mineralization process difficult. Furthermore, the dissolution kinetics of multiple elements interfere with each other during simultaneous release, making it difficult to achieve a single, precise, and stable supply of strontium.

[0005] In terms of preparation processes, existing technologies also suffer from problems such as complex procedures and high energy consumption. Most technologies employ a simple mixing-forming-sintering process, with relatively rudimentary sintering temperature and pressure conditions. Some technologies require prolonged sintering at temperatures above 1000℃ to obtain a stable structure, resulting in high energy consumption. Furthermore, there is a lack of systematic design for pretreatment methods for different raw materials, failing to fully leverage the functional synergistic effects of each mineral component.

[0006] In terms of product form and application, existing mineralization materials are mostly made into filter cartridges, carbon rods, and mineralization balls, which need to be installed in water purification equipment to achieve mineralization through dynamic water flow. This application mode is dependent on equipment, has limited application scenarios, and the dissolution rate of mineral elements in dynamic water flow is easily affected by conditions such as pH, temperature, and flow rate of the raw water, making it difficult to achieve precise and stable control of strontium concentration. Although a few studies have attempted to use mineral powder in the form of tea bags, short-term brewing makes it difficult to fully release mineral elements, and powder seepage can also lead to water turbidity and sedimentation, seriously affecting the user experience.

[0007] In summary, the existing technology lacks a mineralized material with simplified components, controllable process, and the ability to achieve continuous and stable leaching of strontium in daily static immersion scenarios, as well as its preparation method. Summary of the Invention

[0008] To address the aforementioned issues, this invention proposes a novel strontium supplementation technology. It utilizes pulverized and low-temperature calcined natural ore as raw material. Quartz is added to adjust the porosity of the tablets, and calcination generates microcracks or crystal defects. These defects can modulate the porosity characteristics of the material, further influencing the release rate. In everyday scenarios, the tablets achieve continuous and stable dissolution of strontium through soaking, with the dissolution concentration controllable within the range of ≥1 mg / L. This provides a more reliable, convenient, and dosage-defined solution for daily trace element supplementation.

[0009] The first aspect of the present invention provides a mineral water treatment tablet for sustainable strontium leaching, wherein, by mass fraction, the mineral water treatment tablet for sustainable strontium leaching comprises: 10-30% celestite extract, 20-40% strontium ore extract, 10-30% magnesite extract, 0.5-15% quartz, and 10-30% binder. Celestite extract is strontium sulfate powder obtained by calcining celestite at 620-750℃; low-temperature calcination of celestite induces lattice distortion and increases Sr. 2+ Displacement activity.

[0010] The strontium ore extract is strontium carbonate powder obtained by calcining strontium ore at 400-500℃; the strontium ore undergoes metastable decomposition by low-temperature calcination, retaining some carbonate skeleton to regulate the dissolution rate.

[0011] Magnesite extract is a magnesium salt obtained by calcining magnesite at 1000-1100℃.

[0012] Furthermore, the main component of the celestite extract in this application is strontium sulfate, the main component of strontium sapphire is strontium carbonate, and the main chemical component of natural magnesite is magnesium carbonate. Through incomplete decomposition of the celestite extract by calcination, the material is in a metastable state of structural activation, which can increase the stable dissolution of strontium from the material. After calcination, the strontium sapphire extract is transformed into a composite phase of SrO·SrCO3, which can adjust the dissolution rate of strontium ions. Natural magnesite, after calcination, mainly generates highly chemically active magnesium salts. Simultaneously, calcination can increase the specific surface area of ​​the material and form a porous structure, achieving continuous and stable dissolution of strontium.

[0013] Optionally, by mass fraction, the mineral water treatment tablets for continuously leaching strontium comprise: 15-25% celestite extract, 25-35% strontium ore extract, 15-25% magnesite extract, 5-10% quartz, and 15-25% binder.

[0014] Optionally, the mass ratio of celestite extract, strontium ore extract, and magnesite extract is 1:1.5:1.

[0015] Optionally, the celestite extract is strontium sulfate powder obtained by calcining celestite at 650-720℃; Strontium ore extract is strontium carbonate powder obtained by calcining strontium ore at 430-470℃; Magnesite extract is a magnesium salt obtained by calcining magnesite at 1030-1070℃.

[0016] For example, celestite can be calcined at any temperature, or within any range of two points, from 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, 710℃, 720℃, 730℃, 740℃, or 750℃ to obtain strontium sulfate powder. Strontium carbonate can be calcined at any temperature, or within any range of two points, from 400℃, 405℃, 410℃, 415℃, 420℃, 425℃, 430℃, 435℃, 440℃, 445℃, 450℃, 455℃, 460℃, 465℃, 470℃, 475℃, 480℃, 485℃, 490℃, 495℃, or 500℃ to obtain strontium carbonate powder. Magnesite can be calcined at any point or within any range of 1000℃, 1010℃, 1020℃, 1030℃, 1040℃, 1050℃, 1060℃, 1070℃, 1080℃, 1090℃ or 1100℃ to obtain magnesium salts.

[0017] Optionally, when the mineral water treatment tablets are statically immersed in 250mL of pure water at 20-30℃, the strontium ion concentration in the immersion solution is maintained above 1ppm for 1 hour.

[0018] Optionally, in the dynamic service life test, after soaking the mineral water treatment tablet in 250mL of pure water for 20 minutes and then replacing it with fresh water, and after completing a total of 120 cycles, the strontium ion dissolution amount can be stably maintained above 1ppm.

[0019] Optionally, the adhesive is silica sol.

[0020] A second aspect of this invention provides a method for preparing a mineral water treatment tablet with sustainable strontium dissolution, comprising the following steps: S1: Magnesite extract is mixed with quartz and pre-sintered at 800-850℃ to obtain pre-sintered material; the pre-sintered material is processed into a metastable state to adjust the dissolution rate of subsequent materials.

[0021] S2: Mix the pre-sintered materials, celestite extract, and strontium ore extract, add a binder and knead to form a wet billet; Furthermore, the particle size of the mixed powder is 200-400 mesh. The particle size of the raw materials is controlled through physical methods to increase the specific surface area and enhance the activity of subsequent reactions.

[0022] S3: The wet billet is subjected to three-stage pressure forming: the first stage is pressured at 5-10MPa, the second stage at 20-30MPa, and the third stage at 40-50MPa to obtain a sheet-like green billet. To elaborate further, the process involves three stages: first, low pressure (5-10 MPa) to rearrange the particles; second, medium pressure (20-30 MPa) to densify the green body; and third, high pressure (40-50 MPa) with a holding time of 30 seconds to eliminate internal macroscopic defects. This pressing process yields a sheet-like mineralized green body with high green body strength.

[0023] S4: The sheet-shaped green body is subjected to gradient sintering to obtain the mineral water treatment sheet.

[0024] For example, the temperature for pre-sintering magnesite extract with quartz can be any point value or a range between any two points from 800℃, 805℃, 810℃, 815℃, 820℃, 825℃, 830℃, 835℃, 840℃, 845℃ or 850℃.

[0025] Optionally, gradient sintering includes the following steps: heating to 280-320℃ at a heating rate of 0.5-2℃ / min and holding at that temperature for 90-150 minutes; Then raise the temperature to 620-680℃ at a rate of 2-5℃ / min and hold for 150-210 minutes; Finally, the temperature is increased to 830-870℃ at a rate of 1-3℃ / min and held for 45-90 minutes, followed by rapid cooling.

[0026] To elaborate further, the temperature is raised to 280-320℃ at a heating rate of 0.5-2℃ / min and held for 90-150 minutes to slowly expel the pore-forming agent and form initial interconnected pores. Then, the temperature is raised to 620-680℃ at a heating rate of 2-5℃ / min and held for 150-210 minutes to promote interfacial reactions between the mineral phases and generate a new calcium-strontium composite silicate phase. Finally, the temperature is raised to 830-870℃ at a heating rate of 0.5-2℃ / min and held for 45-90 minutes. The lid is then opened and the temperature is rapidly cooled to lock in the high-temperature phase structure, forming a gradient microstructure with a glassy surface and porous interior.

[0027] The third aspect of the present invention provides the application of the above-mentioned mineral water treatment tablets or the mineral water treatment tablets prepared by the above-mentioned preparation method in the preparation of strontium mineralized products for drinking water.

[0028] Compared with the prior art, the present invention achieves at least one of the following beneficial effects: (1) This invention is made from natural mineral raw materials through physical processing. It does not involve complex systems such as electrolysis, so there are no electrical safety hazards, nor are there any problems with the taste caused by electrolysis byproducts (active oxygen and hydrogen). The product is in the form of flakes, and no powder seeps out during the soaking process, which avoids the water turbidity and sedimentation problems caused by traditional mineral powder tea bags, and has high market acceptance.

[0029] (2) This invention uses only four mineral raw materials—celestite powder, strontium ore powder, magnesite powder, and quartz—and a binder to form a simplified formula. Each component has a clear function and division of labor. Celestite and strontium ore serve as dual strontium sources, providing strontium. Magnesite reacts with quartz during sintering to form a forsterite transition phase, providing structural support. Quartz also plays a role in porosity regulation. This achieves a precise and stable supply of strontium.

[0030] (3) The mineral water treatment tablets of this invention, which continuously dissolve strontium, form a gradient microstructure with a glassy surface and porous interior. When each tablet is statically immersed in 250 mL of pure water at 20-30°C, the strontium ion concentration in the immersion solution remains above 1 ppm for 1 hour. In the dynamic service life test, after 120 cycles of immersion in 250 mL of pure water for 20 minutes followed by replacement with fresh water, the strontium ion dissolution rate remained stable above 1 ppm. Attached Figure Description

[0031] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this invention, illustrate exemplary embodiments of the invention and are used to explain the invention, but do not constitute an undue limitation of the invention. In the drawings: Figure 1An exemplary embodiment of the mineral water treatment tablet product with sustainably leached strontium prepared according to Example 1 of the present invention is shown; Figure 2 An exemplary embodiment of the mineral water treatment tablet product with sustainably leached strontium prepared in Example 4 is shown. Detailed Implementation

[0032] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0033] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application were all purchased commercially.

[0034] Unless otherwise specified, the methods used in the embodiments and comparative examples of this application are conventional methods in the prior art.

[0035] Example 1 In an exemplary embodiment of the present invention, the mineral water treatment tablet for continuously leaching strontium comprises, by mass fraction: 20% celestite extract, 30% strontium ore extract, 20% magnesite extract, 10% quartz, and 20% silica sol.

[0036] The preparation method includes the following steps: Step 1: Raw material pretreatment: Celestite extract, strontium spar extract, magnesite extract, and quartz are crushed and ground separately to control the particle size to 300 mesh, ensuring the consistency and controllability of subsequent reactions. Magnesite extract and quartz are mixed and pre-sintered at 830℃ to obtain pre-sintered material.

[0037] Among them, celestite extract is strontium sulfate powder obtained by calcining celestite at 700℃, strontium ore extract is strontium carbonate powder obtained by calcining strontium ore at 450℃, and magnesite extract is magnesium salt obtained by calcining magnesite ore at 1050℃.

[0038] Step 2, Mixing and Preform Formation: After mixing the powder obtained in Step 1, silica sol is added. The mixture is thoroughly stirred and kneaded to ensure complete contact between the powder and silica sol, forming a wet preform with a certain degree of plasticity and uniformity. This plastic wet preform provides a suitable material state for subsequent molding. Simultaneously, the selection and distribution of the binder have a significant impact on the pore structure and strength of the final material, thereby indirectly controlling the strontium dissolution rate.

[0039] Step 3, Multi-stage Press Molding and Drying: Pressing process yields a green body with certain structural strength and stable shape. The green body obtained in Step 2 is placed in a precision hydraulic press and subjected to three-stage pressurization: First stage: low pressure (8MPa), to rearrange particles; Second stage: medium pressure (25 MPa), to densify the green body; Third stage: high pressure (45 MPa) and held for 30 seconds to eliminate internal macroscopic defects.

[0040] Step 4: Press to obtain a sheet-like mineralized material green body with high green body strength. Place the green body in a kiln for staged gradient sintering: raise the temperature to 300℃ at a heating rate of 1℃ / min and hold for 120 minutes to slowly remove the pore-forming agent and form initial interconnected pores; then raise the temperature to 650℃ at a heating rate of 3℃ / min and hold for 180 minutes to promote interfacial reactions between mineral phases and generate a new calcium-strontium composite silicate phase; finally, raise the temperature to 850℃ at a heating rate of 2℃ / min and hold for 60 minutes, then open the lid for rapid cooling to lock in the high-temperature phase structure and form a gradient microstructure with a glassy surface and porous interior. (See the product image of the mineral water treatment sheet prepared in Example 1 for reference.) Figure 1 As shown.

[0041] The material prepared in Example 1 underwent systematic testing. Table 1 shows the static dissolution stability test: At room temperature, a mineralized water sample with a diameter of 45 mm and a thickness of 7 mm was placed in 250 mL of pure water and allowed to stand. After soaking for 0.5 hours, 1 hour, and 2 hours, the soaking solution was collected and the strontium ion concentration was measured. Table 2 shows the dynamic service life test: At room temperature, a mineralized water sample was taken and the following operation was repeated: it was soaked in 250 mL of pure water for 20 minutes, then the water sample was removed and the strontium ion content in the soaking solution was measured; then 250 mL of new pure water was replaced, and the above soaking and testing process was repeated. This cycle was repeated continuously until a total of 120 cycles were completed, thereby systematically examining the decay of strontium ion dissolution during the entire service life of the material.

[0042] Table 1

[0043] Table 2

[0044] Referring to Tables 1 and 2, when the mineral water treatment tablets were statically immersed in 250mL of pure water at 20-30℃, the strontium ion concentration in the immersion solution reached above 1ppm after 1 hour, and remained at 2.5-3ppm after 2 hours. In the dynamic lifespan test, after 120 cycles of immersion in 250mL of pure water for 20 minutes followed by water replacement, the strontium ion dissolution remained stable above 1ppm.

[0045] Example 2 In an exemplary embodiment of the present invention, the mineral water treatment tablet for continuously leaching strontium comprises, by mass fraction: 30% celestite extract, 40% strontium ore extract, 10% magnesite extract, 10% quartz, and 10% silica sol.

[0046] The preparation method includes the following steps: Step 1: Raw material pretreatment and mixing: Celestite extract, strontium ore extract, magnesite extract, and quartz are crushed and ground separately to control the powder particle size to 200 mesh. Magnesite extract and quartz are mixed and pre-sintered at 800℃ to obtain pre-sintered material.

[0047] Among them, celestite extract is strontium sulfate powder obtained by calcining celestite at 650℃, strontium ore extract is strontium carbonate powder obtained by calcining strontium ore at 400℃, and magnesite extract is magnesium salt obtained by calcining magnesite ore at 1000℃.

[0048] Step 2, Mixing and Preparing: After mixing the powder obtained in Step 1, add silica sol, and after thorough stirring and mixing, obtain wet ingredients.

[0049] Step 3, Multi-stage pressure molding and drying: Place the wet blank obtained in step 2 into a precision hydraulic press and apply pressure in three stages: first stage: low pressure (5MPa); second stage: medium pressure (20 MPa); third stage: high pressure (40MPa) and hold for 30 seconds.

[0050] Step 4: Place the pressed green body in a kiln and perform staged gradient sintering: raise the temperature to 280℃ at a heating rate of 0.5℃ / min and hold for 90 minutes; then raise the temperature to 620℃ at a heating rate of 2℃ / min and hold for 150 minutes; finally raise the temperature to 830℃ at a heating rate of 1℃ / min and hold for 45 minutes, then open the lid and cool rapidly to obtain a mineral water treatment sheet that can continuously leach strontium.

[0051] The material prepared in Example 2 was subjected to systematic testing. Table 3 shows the static dissolution stability test: At room temperature, a mineralized water sample with a diameter of 45 mm and a thickness of 7 mm was placed in 250 mL of pure water and allowed to stand. The soaking solution was collected and the strontium ion concentration was measured after soaking for 0.5 hours and 1 hour, respectively.

[0052] Table 3

[0053] As shown in Table 3, when the mineral water treatment tablets are statically immersed in 250mL of pure water at 20-30℃, the strontium ion concentration in the immersion solution reaches more than 1ppm in 1 hour.

[0054] Example 3 In an exemplary embodiment of the present invention, the mineral water treatment tablet for continuously leaching strontium comprises, by mass fraction: 10% celestite extract, 40% strontium ore extract, 30% magnesite extract, 10% quartz, and 10% silica sol.

[0055] The preparation method includes the following steps: Step 1: Raw material pretreatment and mixing: Celestite extract, strontium ore extract, magnesite extract, and quartz are crushed and ground separately to control the powder particle size to 400 mesh. Magnesite extract and quartz are mixed and pre-sintered at 800℃ to obtain pre-sintered material.

[0056] Among them, celestite extract is strontium sulfate powder obtained by calcining celestite at 750℃, strontium ore extract is strontium carbonate powder obtained by calcining strontium ore at 500℃, and magnesite extract is magnesium salt obtained by calcining magnesite ore at 1100℃.

[0057] Step 2, Mixing and Preparing: After mixing the powder obtained in Step 1, add silica sol, and after thorough stirring and mixing, obtain wet ingredients.

[0058] Step 3, Multi-stage pressure molding and drying: Place the wet blank obtained in step 2 into a precision hydraulic press and apply pressure in three stages: first stage: low pressure (10MPa); second stage: medium pressure (30 MPa); third stage: high pressure (50MPa) and hold for 30 seconds.

[0059] Step 4: Place the pressed green body in a kiln and perform staged gradient sintering: raise the temperature to 320℃ at a heating rate of 2℃ / min and hold for 150 minutes; then raise the temperature to 680℃ at a heating rate of 5℃ / min and hold for 210 minutes; finally raise the temperature to 870℃ at a heating rate of 3℃ / min and hold for 90 minutes, then open the lid and cool rapidly to obtain a mineral water treatment sheet that can continuously leach strontium.

[0060] The material prepared in Example 3 was subjected to systematic testing. Table 4 shows the static dissolution stability test: At room temperature, a mineralized water sample with a diameter of 45 mm and a thickness of 7 mm was placed in 250 mL of pure water and allowed to stand. The soaking solution was collected and the strontium ion concentration was measured after soaking for 0.5 hours and 1 hour, respectively.

[0061] Table 4

[0062] As shown in Table 4, when the mineral water treatment tablets are statically immersed in 250mL of pure water at 20-30℃, the strontium ion concentration in the immersion solution reaches more than 1ppm in 1 hour.

[0063] Example 4 Based on Example 1, the main difference lies in step 4, pressing to obtain a sheet-like mineralized material green body with high green body strength. The green body is placed in a kiln for staged gradient sintering: the temperature is raised to 200°C at a heating rate of 1°C / min and held for 120 minutes; then the temperature is raised to 600°C at a heating rate of 3°C / min and held for 180 minutes; finally, the temperature is raised to 800°C at a heating rate of 2°C / min and held for 60 minutes, and then the lid is opened for rapid cooling.

[0064] The mineral water treatment sheet prepared in this embodiment failed to achieve its vitrification transformation due to a low sintering temperature, which did not reach the material's melting point, resulting in a low overall strength. (See product image for reference.) Figure 2 As shown, cracks appear at the edges.

[0065] Example 5 Based on Example 1, the main difference lies in step 4, pressing to obtain a sheet-like mineralized material green body with high green body strength. The green body is placed in a kiln and subjected to staged gradient sintering: the temperature is raised to 350°C at a heating rate of 1°C / min and held for 120 minutes; then the temperature is raised to 700°C at a heating rate of 3°C / min and held for 180 minutes; finally, the temperature is raised to 900°C at a heating rate of 2°C / min and held for 60 minutes, and then the lid is opened for rapid cooling.

[0066] The material prepared in Example 5 was subjected to systematic testing. Table 5 shows the static dissolution stability test: At room temperature, a mineralized water sample with a diameter of 45 mm and a thickness of 7 mm was placed in 250 mL of pure water and allowed to stand. The soaking solution was collected and the strontium ion concentration was measured after soaking for 0.5 hours and 1 hour, respectively.

[0067] Table 5

[0068] As shown in Table 5, when the mineral water treatment tablets are statically soaked in 250mL of pure water at 20-30℃, the concentration of strontium ions in the soaking solution is too low.

[0069] Example 6 Based on Example 1, the main difference is that in step 4, the sheet-like mineralized material green body with high green body strength is directly sintered at a temperature of 650°C and held for 150 minutes.

[0070] The sintering conditions in this embodiment are insufficient to vitrify the green body, resulting in sheet material with excessively low strength.

[0071] Example 7 Based on Example 1, the main difference is that in step 1, the celestite extract, strontium ore extract, magnesite extract and quartz are crushed and ground respectively to control the powder particle size to 200 mesh.

[0072] If the mesh count is too low, the green body cannot maintain its sheet shape when it melts under the sintering conditions of Example 1.

[0073] Comparative Example 1 The main difference from Example 1 is that the celestite extract is strontium sulfate powder of celestite calcined at 600°C.

[0074] The material prepared in Comparative Example 1 was subjected to systematic testing. Table 6 shows the static dissolution stability test: At room temperature, a mineralized water sample with a diameter of 45 mm and a thickness of 7 mm was placed in 250 mL of pure water and allowed to stand. The soaking solution was collected and the strontium ion concentration was measured after soaking for 0.5 hours and 1 hour, respectively.

[0075] Table 6

[0076] As shown in Table 6, strontium ions cannot be stably dissolved when mineral water treatment tablets are statically immersed in 250mL of pure water at 20-30℃.

[0077] Comparative Example 2 The main difference from Example 1 is that the celestite extract is strontium sulfate powder of celestite calcined at 800°C.

[0078] The material prepared in Comparative Example 2 was subjected to systematic testing. Table 7 shows the static dissolution stability test: At room temperature, a mineralized water sample with a diameter of 45 mm and a thickness of 7 mm was placed in 250 mL of pure water and allowed to stand. The soaking solution was collected and the strontium ion concentration was measured after soaking for 0.5 hours and 1 hour, respectively.

[0079] Table 7

[0080] Referring to Table 7, excessively high calcination temperatures result in a more stable and complete crystal lattice structure, making it difficult for strontium ions to dissolve after excessive calcination.

[0081] Comparative Example 3 The main difference from Example 1 is that the strontium ore extract is strontium carbonate powder that has been calcined at 350°C.

[0082] The material prepared in Comparative Example 3 was subjected to systematic testing. Table 8 shows the static dissolution stability test: At room temperature, a mineralized water sample with a diameter of 45 mm and a thickness of 7 mm was placed in 250 mL of pure water and allowed to stand. The soaking solution was collected after 0.5 hours and 1 hour, and the concentration of strontium ions in it was measured.

[0083] Table 8

[0084] Referring to Table 8, the lower calcination temperature cannot form metastable strontium carbonate, resulting in the finished water flakes not being able to achieve stable dissolution.

[0085] Comparative Example 4 Based on Example 1, the main difference lies in the absence of pre-sintering of the magnesite extract and quartz. The strontium ion dissolution performance of uncalcined and pre-calcined strontium flakes after 10 min of soaking was compared. The results show that pre-calcination treatment significantly accelerates the strontium ion dissolution rate.

[0086] Table 9

[0087] Comparative Example 5 Based on Example 1, the main difference is that in step 3, the billet obtained in step 2 is placed in a precision hydraulic press and pressurized in two stages: the first stage is low pressure (8MPa); the second stage is medium pressure (25MPa) and held for 30 seconds to obtain a green billet.

[0088] This comparative example was not subjected to high-pressure pressing, resulting in insufficient green body strength, making it impossible to fire.

[0089] Comparative Example 6 Based on Example 1, the main difference is that in step 3, the billet obtained in step 2 is placed in a precision hydraulic press and pressurized in two stages: the first stage is low pressure (8MPa); the second stage is high pressure (45MPa) and held for 30 seconds to obtain a green billet.

[0090] The green embryo obtained in this comparative example cracked during firing and could not maintain an intact water sheet state.

[0091] Comparative Example 7 Based on Example 1, the main difference is that in step 3, the billet obtained in step 2 is placed in a precision hydraulic press and pressurized in two stages: the first stage is medium pressure (25 MPa); the second stage is high pressure (45 MPa) and held for 30 seconds to obtain a green billet.

[0092] Although this comparative example can obtain a fully formed green body, the surface of the green body cracks and peels during the drying process.

[0093] Test case The mineral water treatment tablets prepared in the above embodiments and comparative examples were subjected to performance tests. The test methods were the same as in Example 1. The strontium ion content in the soaking solution after soaking for 1 hour is shown in the table below.

[0094]

[0095] Referring to the table above, as shown in Examples 1-3, when the mineral water treatment tablets prepared by this invention are statically immersed in 250mL of pure water at 20-30℃, the strontium ion concentration in the immersion solution remains above 1 ppm for 1 hour. In the dynamic service life test, after 120 cycles of immersion in 250mL of pure water for 20 minutes followed by water replacement, the strontium ion dissolution rate remains stable above 1 ppm. The mineral water treatment tablets of this invention achieve efficient and stable strontium dissolution under static immersion conditions at room temperature (20-30℃). The target dissolution concentration is reached within a very short time (0.5h) of contact between the mineral water treatment tablets and the water, and the concentration fluctuation is minimal within 2 hours.

[0096] Referring to Comparative Examples 1 and 2, it is demonstrated that celestite calcination temperature that is too low cannot induce sufficient lattice distortion to improve Sr 2+ The substitution activity is high, but excessively high temperatures can lead to the formation of an overly complete and stable crystal lattice structure, making it difficult for strontium ions to dissolve. Both excessively high and excessively low calcination temperatures of celestite can affect the sustained-release performance of strontium ions.

[0097] As shown in Comparative Example 3, when the calcination temperature of strontium ore is too low, a metastable structure cannot be formed, and the dissolution of strontium cannot be controlled by slow release.

[0098] As shown in Comparative Example 4, the strontium dissolution rate in the control group without pre-sintering was only 0.141 mg / L after immersion for 10 minutes, while the dissolution rate in the pre-sintered group was significantly increased under the same conditions. This demonstrates that the pre-sintering step is crucial for activating the interfacial reaction between magnesite and quartz and generating the in-situ forsterite transition phase. Without pre-sintering, the material lacks a structural support phase, resulting in obstructed strontium ion release channels.

[0099] Referring to Comparative Examples 5-7, this invention demonstrates that through the synergistic effect of low-pressure particle rearrangement, medium-pressure densification, and high-pressure defect elimination, a green body with a complete, uniform, dense structure and free of macroscopic defects is prepared, providing a foundation for subsequent gradient sintering. The three-stage pressure molding process further ensures the strength properties of the sheet, thereby guaranteeing the controlled release of strontium ions.

[0100] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention should be included within the scope of the claims of the present invention.

Claims

1. A mineral water treatment tablet for sustainable strontium dissolution, characterized in that, The mineral water treatment tablets for continuously leaching strontium, by mass fraction, comprise: 10-30% celestite extract, 20-40% strontium ore extract, 10-30% magnesite extract, 0.5-15% quartz, and 10-30% binder. Celestite extract is strontium sulfate powder obtained by calcining celestite at 620-750℃; Strontium ore extract is strontium carbonate powder obtained by calcining strontium ore at 400-500℃; Magnesite extract is a magnesium salt of magnesite that has been calcined at 1000-1100℃.

2. The mineral water treatment tablet for sustainable strontium dissolution according to claim 1, characterized in that, The mineral water treatment tablets for continuously leaching strontium, by mass fraction, comprise: 15-25% celestite extract, 25-35% strontium ore extract, 15-25% magnesite extract, 5-10% quartz, and 15-25% binder.

3. The mineral water treatment tablet for sustainable strontium dissolution according to claim 1, characterized in that, The mass ratio of celestite extract, strontium ore extract, and magnesite extract is 1:1.5:

1.

4. The mineral water treatment tablet for sustainable strontium leaching according to claim 1, characterized in that, Celestite extract is strontium sulfate powder obtained by calcining celestite at 650-720℃. Strontium ore extract is strontium carbonate powder obtained by calcining strontium ore at 430-470℃; Magnesite extract is a magnesium salt of magnesite that has been calcined at 1030-1070℃.

5. The mineral water treatment tablet for sustainable strontium dissolution according to claim 1, characterized in that, When the mineral water treatment tablets are statically immersed in 250mL of pure water at 20-30℃, the strontium ion concentration in the immersion solution remains above 1 ppm for 1 hour. And / or the mineral water treatment tablets, after being soaked in 250mL of pure water for 20 minutes and then replaced with fresh water, after a total of 120 cycles, showed that the strontium ion dissolution was stable at over 1ppm.

6. A method for preparing a mineral water treatment tablet for the sustainable dissolution of strontium as claimed in any one of claims 1-5, characterized in that, Includes the following steps: S1: Mix magnesite extract with quartz and pre-sinter at 800-850℃ to obtain pre-sintered material; S2: Mix the pre-sintered materials, celestite extract, and strontium ore extract, add a binder and knead to form a wet billet; S3: The wet billet is subjected to three-stage pressure forming: the first stage is pressured at 5-10MPa, the second stage at 20-30MPa, and the third stage at 40-50MPa to obtain a sheet-like green billet. S4: The sheet-shaped green body is subjected to gradient sintering to obtain the mineral water treatment sheet.

7. The preparation method according to claim 6, characterized in that, Step S4, gradient sintering includes the following steps: heating to 280-320℃ at a heating rate of 0.5-2℃ / min and holding at that temperature for 90-150 minutes; Then raise the temperature to 620-680℃ at a rate of 2-5℃ / min and hold for 150-210 minutes; Finally, raise the temperature to 830-870℃ at a rate of 1-3℃ / min and hold for 45-90 minutes, then cool.

8. The preparation method according to claim 6, characterized in that, In step S2, the particle size of the mixed powder is 200-400 mesh.

9. The preparation method according to claim 6, characterized in that, The binder is silica sol.

10. The use of a mineral water treatment tablet as described in any one of claims 1-5 or a mineral water treatment tablet prepared by the preparation method as described in any one of claims 6-9 in the preparation of strontium mineralized drinking water products.

Citation Information

Patent Citations

  • Strontium-rich mineralized filter element with high flux and long service life and preparation method thereof

    CN114470889A

  • A slow-release mineralization material capable of dissolving alkali metals / strontium / selenium elements and a preparation method thereof

    CN117164337B

  • Strontium mineralized slow-release filter element and preparation method thereof, and water purifier

    CN117942664B